Performance measurement systems in the health sector and their budgetary implications - Beazley, Ivor (OECD Publishing, 2019)
This article looks at the application of performance measurement systems in the health sector across OECD countries. The data comes from the 2017 OECD Survey on Performance Measurement Systems in the Health Sector and Responsibilities across Levels of Government. The results show that the majority of countries have national performance measurement systems in place, covering multiple aspects of the health system. Despite varying objectives, measurement systems are usually aimed at improving performance of the health system, rather than at containing costs
Keywords: Finance and Investment; Governance; Social Issues/Migration/Health; Economics